2005
DOI: 10.5194/hess-9-685-2005
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution phosphorus transfers at the catchment scale: the hidden importance of non-storm transfers

Abstract: High-resolution measurements of total phosphorus (TP) concentrations in a stream draining a 5 km 2 agricultural catchment (a sub-catchment of Lough Neagh in Northern Ireland) were made every 10 mins by continuous flow instrumentation using new homogenisation, digestion and colorimetric phases. Concurrently, rainfall and stream discharge data were collected at 5 and 15 min. intervals. Major P flushing episodes during storm events peaked on the rising limbs of storm hydrographs. A period of baseflow also indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
114
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(120 citation statements)
references
References 12 publications
5
114
0
Order By: Relevance
“…Many researchers (e.g. Harris and Heathwaite, 2005;Heathwaite, 2010;Johnes, 2007;Jordan et al, 2005a) have identified the need for small scale and short timestep data in order to unravel the complex processes of nutrient cycling in headwaters. Headwater catchments are very dynamic and their responses may be misrepresented by infrequent, low intensity sampling regimes (Cassidy and Jordan, 2011;Defew et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers (e.g. Harris and Heathwaite, 2005;Heathwaite, 2010;Johnes, 2007;Jordan et al, 2005a) have identified the need for small scale and short timestep data in order to unravel the complex processes of nutrient cycling in headwaters. Headwater catchments are very dynamic and their responses may be misrepresented by infrequent, low intensity sampling regimes (Cassidy and Jordan, 2011;Defew et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Until now, the majority of research in Ireland has focused on quantifying nutrient and, to a lesser extent, sediment losses from permanent grassland at laboratory- (Doody et al 2006;Murphy 2007;Murphy and Stevens 2010), plot/field- (Tunney et al 2007;Kurz et al 2000;Douglas et al 2007) and catchment-scales (Smith et al 1995;Scanlon et al 2004;Jordan et al 2005a;2005b;Smith et al 2005;Jordan et al 2007). Modelling of diffuse P loss from grassland catchments has also been undertaken by Jordan et al (2000), Daly et al (2002), Scanlon et al (2005) and Nasr et al (2007), with the aim of improving management strategies to minimise P loss.…”
Section: Research To Date On Sediment and P Lossmentioning
confidence: 99%
“…These situations include large rivers (Tank et al 2008), wetlands, and the changing background conditions of flow and chemistry that often define lotic ecosystems. For example, storm-flushing of nutrients (Jordan et al 2005), including episodic transport of soluble P (Fig. 1), can be common in agricultural catchments and may contribute substantially to annual river loads.…”
Section: Introductionmentioning
confidence: 99%